2014
DOI: 10.1210/jc.2014-1302
|View full text |Cite
|
Sign up to set email alerts
|

Nodules in Autoimmune Thyroiditis Are Associated With Increased Risk of Thyroid Cancer in Surgical Series But Not in Cytological Series: Evidence for Selection Bias

Abstract: The results of our cytological series do not support a link between N-AIT and thyroid cancer. The association between cancer and N-AIT found in the histology-based series is likely due to a selection bias represented by the fact that the prevalent indication for surgery in the N-AIT group was suspicious cytology (60.7% of patients) more frequently than in the other groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 25 publications
5
30
1
Order By: Relevance
“…The authors underline that a selection bias may account for the higher prevalence of PTC in HT in histological series, because in the vast majority of these patients, the indication for surgery is the presence of nodules suspicious for malignancy, while it is more commonly the size of goiter or the presence of compressive symptoms in patients with nodular goiter. These findings were confirmed by Castagna et al [47] who reported that the prevalence of malignant cytology in patients with nodular HT diagnosed on clinical grounds was similar (4.5%) to that found in nodular goiter with or without TAb and in nodular Graves' disease (GD). When the same analysis was performed in the subgroup of patients submitted to thyroid surgery, the prevalence of PTC was significantly higher in patients with nodular HT (67.8%) compared with the other groups (36.9, 37.2 and 40%, respectively).…”
Section: Thyroid Autoimmunity and Ptcsupporting
confidence: 75%
“…The authors underline that a selection bias may account for the higher prevalence of PTC in HT in histological series, because in the vast majority of these patients, the indication for surgery is the presence of nodules suspicious for malignancy, while it is more commonly the size of goiter or the presence of compressive symptoms in patients with nodular goiter. These findings were confirmed by Castagna et al [47] who reported that the prevalence of malignant cytology in patients with nodular HT diagnosed on clinical grounds was similar (4.5%) to that found in nodular goiter with or without TAb and in nodular Graves' disease (GD). When the same analysis was performed in the subgroup of patients submitted to thyroid surgery, the prevalence of PTC was significantly higher in patients with nodular HT (67.8%) compared with the other groups (36.9, 37.2 and 40%, respectively).…”
Section: Thyroid Autoimmunity and Ptcsupporting
confidence: 75%
“…Some retrospective cytological studies analyzed by Castagna et al [55] and Matesa-Anić et al [56] did not find an increased risk of thyroid cancer in patients with HT. In the latter study, the prevalence of PTC was lower in HT patients (1.9%) than in patients without HT (2.7%); the same result was also confirmed by a previous FNAC prospective study [57].…”
Section: Association Of Ptc and Ht: Clinical Studiesmentioning
confidence: 99%
“…However, this relationship was not reported in a limited number of studies (10,11). In large part of the studies based on the cytological examination results of FNAB, it is reported that incidence of PTC is not increased in HT patients and HT is not a risk factor for PTC (12,13). In a literature review performed at 2013, coexistence of HT with PTC was reported as 27.56% in studies based on histopathologic results of thyroidectomy specimens, and 1.2% in studies based on cytological results of FNAB.…”
Section: Discussionmentioning
confidence: 99%